Long non-coding RNAs as a biomarker for homologous recombination deficiency and parp inhibitor sensitivity in high-grade serous ovarian cancers - Doberstein, Kai; Panther, Johannes; Hahnen, Eric; Richters, Lisa; Schouten, Philip; Harter, Philipp; Heitz, Florian; Kommoss, Stefan; Berlit, Sebastian; Tuschy, Benjamin; Sütterlin, Marc; Marmé, Frederik (Communications biology, 2025)
Homologous recombination deficiency (HRD) and sensitivity to PARP inhibitors are key determinants of therapeutic response in high-grade serous ovarian cancer (HGSC), yet predictive biomarkers beyond BRCA1/2 mutations or genomic HRD scores remain inadequate. Here, we investigate the potential of long non-coding RNAs (lncRNAs) as predictive markers of HRD and PARP inhibitor response. We identify a panel of lncRNAs that stratifies HGSC tumors by HRD status and drug sensitivity. Among these, ENSG00000272172.1 is significantly upregulated in HRD-positive tumors and is detectable in both formalin-fixed tissue and plasma, supporting its use as a minimally invasive biomarker. Functional analyses reveal that this lncRNA contributes to genome stability by modulating replication dynamics. These findings highlight a previously unrecognized role for lncRNAs in the HRD phenotype and suggest translational potential for ENSG00000272172.1 in guiding clinical decision-making.
Gesehen am 18.12.2025